88 Dietary supplementation of branched-chain amino acids higher than recommended levels in nursery pigs fed with moderately low protein diet: effects on growth performance. (5th December 2019) - Habibi, Mohammad; Shili, Cedrick N; Sutton, Julia; Pezeshki, Adel
Abstract: Feed cost and excess nutrients excretion are threatening the swine industry. Moderately low protein (MLP) diets are less expensive and reduce the nitrogen excretion, but they may have negative influence on growth performance of pigs. The aim of current study was to investigate the effect of MLP diets supplemented with branched-chain amino acids (BCAA; leucine, isoleucine and valine) higher than Nutrients Requirements of Swine (NRC) recommendation on the growth performance of nursery pigs. Forty-eight weaned barrows at 3 weeks of age were weighed, individually housed and randomly assigned to 6 dietary treatments including: 1) PCON: 20% crude protein (CP), 2) NCON: 14% CP; 3) C25: NCON+ limiting amino acids (LAA, i.e. lysine, methionine, threonine, and tryptophan) 25% more than NRC levels, 4) C50: NCON+LAA 50% higher than NRC recommendations; 5) CB25: NCON + (LAA+BCAA) 25% more than NRC; 6) CB50: NCON + (LAA+BCAA) 50% higher than NRC. The data were analyzed with univariate GLM with Tukey's post-hoc test (SPSS ® ). The CB50 had higher final body weight, average daily gain, average daily water intake and average daily feed intake than C50 with the latter tended to be higher than NCON. Average daily feed intake, average daily gain and gain to feed ratio tended to be greater for CB25 and CB50 relative to C25 and C50, respectively. Compared to C50, CB50 improved the mean and cumulative feed intake in all the weeks. CB50 also tended to improve the body weight gain and gain: feed in week 2 relative to C50. In conclusion, supplementing MLP diets with limiting amino acid at 25% or 50% higher than NRC recommendations was failed to recover the negative effects of these diets on growth performance. Adding BCAA more than NRC levels to MLP diets improved the growth performance with the effects of added BCAA level being negligible.